Effect of Bottom Geometry on the Natural Sloshing Motion of Water inside Tanks: An Experimental Analysis - Antonio Agresta; Nicola Cavalagli; Chiara Biscarini; Filippo Ubertini (Applied Sciences, 2021)
The present work aims at understanding and modelling some key aspects of the sloshing phenomenon, related to the motion of water inside a container and its effects on the substructure. In particular, the attention is focused on the effects of bottom shapes (flat, sloped and circular) and water depth ratio on the natural sloshing frequencies and damping properties of the inner fluid. To this aim, a series of experimental tests has been carried out on tanks characterised by different bottom shapes installed over a sliding table equipped with a shear load cell for the measurement of the dynamic base shear force. The results are useful for optimising the geometric characteristics of the tank and the fluid mass in order to obtain enhanced energy dissipation performances by exploiting fluid–structure interaction effects.